Effects of a ferrate-containing preparation on diverse metabolic processes in yeast - Kotyk, A; Lapathitis, G; Suttajit, M (Folia microbiologica, 2000)
A plant-sap-derived preparation containing bi- and tervalent ferrate anions was tested on growth, respiration on glucose, and membrane transport of 6-deoxy-D-glucose (6-dGlc) and 2-aminoisobutyric acid (Aib) in several yeast species, Saccharomyces cerevisiae, Schizosaccharomyces pombe, Lodderomyces elongisporus, Rhodotorula gracilis, and Dipodascus magnusii. Growth was enhanced by as much as 65%, respiration was not affected significantly except for a decrease in R. gracilis, transport of 6-dGlc was not affected while that of Aib was increased by up to 45% in R. gracilis and up to 27% in L. elongisporus.
Keywords: Aminoisobutyric Acids; buněčná membrána; kinetika; Deoxyglucose; Iron; Yeasts; Plant Extracts; železo; rostlinné extrakty; aktivní transport; kyseliny aminoisomáselné; deoxyglukosa; kvasinky; Biological Transport, Active; Oxygen Consumption; spotřeba kyslíku; Cell Membrane; Kinetics